Sustainable Management of Eremanthus erythropappus in Minas Gerais, Brazil – A Review - Araújo,Emanuel José Gomes de (2018)
ABSTRACT We reviewed key studies published so far regarding Eremanthus erythropappus (DC.) MacLeish (Candeia), in order to approach the sustainable management of this species. The objective of this study was to discuss what is already known by the scientific community, presenting the current scenario and outlining the main challenges that still need to be addressed. Candeia is a tree species found in some Brazilian states, being used in the production of fence posts, and essential oils. It aids in the preservation and restoration of natural areas when properly managed, promoting social development through the creation of jobs and economic growth, due to the current high demand and market value for its products. Due to the high value of its timber, there is a strong anthropic pressure on this species, and it has consequently been exploited in an unsustainable manner. However, already published research suggests that well-managed stands of Eremanthus erythropappus can be economically feasible.